A simple and efficient plasticity-fracture constitutive model for confined concrete - Hadi Meidani (Numerical Methods in Civil Engineering)
A plasticity-fracture constitutive model is presented for prediction of the behavior of confined plain concrete. A three-parameter yield surface is used to define the elastic limit. Volumetric plastic strain is defined as hardening parameter, which together with a nonlinear plastic potential forms a non-associated flow rule. The use of non-associated flow rule improves the prediction of the dilation behavior of concrete under compressive loading. To model the softening behavior, a fracture energy-based function is used to describe strength degradation in post-peak regime. The Euler-forward algorithm is used to integrate the constitutive equations. The proposed model is validated against the results of triaxial compressive experiments. Finally, the behavior of plain concrete confined by layers of carbon fiber reinforced polymer is studied to show capability of the model for passive confinement.